Microcirculation Revisited From Molecules to Clinical Practice - Lenasi, Helena (IntechOpen, 2016)
The book provides a comprehensive overview of selected topics in microcirculation, from physiology to pathophysiology including molecular mechanisms and clinical aspects. It contains 10 chapters written by reputed authors, which comprehensively sum up the current knowledge and some interesting new insights in the field of microcirculation. It will be useful to a broad range of audience, from students to highly profiled experts, helping them to expand their knowledge on microcirculation and opening up additional questions for further investigation.